Role of calcium channels in catecholamine secretion in the rat adrenal gland - Nagayama, Takahiro (Blackwell Science Inc, 1999)
1. We elucidated the contribution of voltage-dependent Ca(2+) channels to cholinergic control of catecholamine secretion in the isolated perfused rat adrenal gland. 2. Nifedipine (0.3–3 μm) inhibited increases in noradrenaline output induced by transmural electrical stimulation (1–10 Hz) and acetylcholine (6–200 μm), whereas it only slightly inhibited the adrenaline output responses. Nifedipine also inhibited the catecholamine output response induced by 1,1-dimethyl-4-phenyl-piperazinium (DMPP; 5-40 μm) but not by methacholine (10–300 μm). 3. ω-Conotoxin MVIIC (10–1000 nm) inhibited the catecholamine output responses induced by electrical stimulation but not by acetylcholine, DMPP and methacholine. 4. ω-Conotoxin GVIA (50–500 nm) had no inhibitory effect on the catecholamine output responses. 5. These results suggest that L-type Ca(2+) channels are responsible for adrenal catecholamine secretion mediated by nicotinic receptors but not by muscarinic receptors, and that their contribution to noradrenaline secretion may be greater than that to adrenaline secretion. P/Q-type Ca(2+) channels may control the secretion at a presynaptic site.